Organic Fluorophores for 1064 nm Excited NIR-II Fluorescence Imaging - Wang, Wenqi; He, Xiaowen; Du, Mingzhi; Xie, Chen; Zhou, Wen; Huang, Wei; Fan, Quli (Frontiers in Chemistry, 2021)
Second near-infrared window (NIR-II) fluorescence imaging has shown great potential in the field of bioimaging. However, the excitation wavelengths of most NIR-II fluorescence dyes are in the first near-infrared (NIR-I) region, which leads to limited imaging depth and resolution. To address such issue, NIR-II fluorescence dyes with 1064 nm excitation have been developed and applied for in vivo imaging. Compared with NIR-I wavelength excited dyes, 1064 nm excited dyes exhibit a higher tissue penetration depth and resolution. The improved performance makes these dyes have much broader imaging applications. In this mini review, we summarize recent advances in 1064 nm excited NIR-II fluorescence fluorophores for bioimaging. Two kinds of organic fluorophores, small molecule dye and semiconducting polymer (SP), are reviewed. The general properties of these fluorophores are first introduced. Small molecule dyes with different chemical structures for variety of bioimaging applications are then discussed, followed by the introduction of SPs for NIR-II phototheranostics. Finally, the conclusion and future perspective of this field is given.